Deep-Breathing Exercise for Reducing Signs and Symptoms of Risk for Violent Behavior in Pediatric Psychiatric Inpatients: A Three-Case Series - Mundakir Mundakir; Septriana Puja Prameswari; Chlara Yunita Prabawati; Anis Rosyiatul Husna (Indonesian Academia Health Sciences Journal, 2026)
Background: Patients with a nursing diagnosis of risk for violent behavior may display verbal threats, aggressive behavior, clenched fists, a rigid posture, facial flushing, and other signs of escalating anger. Deep-breathing exercise is a simple nonpharmacological nursing intervention intended to reduce physical tension and support emotional control. Objective: To describe changes in signs and symptoms of risk for violent behavior and the ability to perform a deep-breathing exercise among three pediatric psychiatric inpatients. Methods: A descriptive case series was conducted in the Lily Ward of Menur Mental Hospital, Surabaya, Indonesia, from June 3 to 23, 2024. Three inpatients aged 10-17 years with a nursing diagnosis of risk for violent behavior received a supervised deep-breathing exercise on seven consecutive days. The core breathing exercise lasted 5 minutes and consisted of sitting comfortably, closing the eyes, inhaling slowly through the nose, holding the breath for 3 seconds, and exhaling slowly through the mouth. Outcomes were observed using a 14-item checklist based on the Indonesian Nursing Diagnosis Standards. Each present sign or symptom was scored 1 and each absent sign or symptom was scored 0. Results: At baseline, Cases 1, 2, and 3 displayed 7/14 (50.0%), 8/14 (57.1%), and 5/14 (35.7%) signs and symptoms, respectively. No reduction was observed on Day 1, when all participants were unwilling to complete the exercise. On Day 2, the respective scores decreased to 5, 6, and 3; on Day 3, to 3, 4, and 1; and on Day 4, to 2, 2, and 0. No observed signs or symptoms were recorded in any participant from Days 5 through 7. All participants partially completed the exercise on Day 2 and completed all procedural steps from Days 3 through 7. Conclusion: Repeated deep-breathing exercise was feasible after an initial engagement period and was accompanied by a progressive reduction in observed signs and symptoms of risk for violent behavior. Because this uncontrolled three-case series cannot establish causality, deep breathing should be considered an adjunct to comprehensive psychiatric and nursing care rather than a replacement for standard treatment.